If λm∞12Zn2+=52.8Scm2mol−1, and Λm∞Zn3Fe(CN)62=922.8Scm2mol−1  The Λm∞Fe(CN)63− will be

# If ${\lambda }_{m}^{\mathrm{\infty }}\left(\frac{1}{2}{\mathrm{Zn}}^{2+}\right)=52.8\mathrm{S}{\mathrm{cm}}^{2}{\mathrm{mol}}^{-1}$, and ${\mathrm{\Lambda }}_{\mathrm{m}}^{\mathrm{\infty }}\left({\mathrm{Zn}}_{3}{\left[\mathrm{Fe}\left(\mathrm{CN}{\right)}_{6}\right]}_{2}\right)=922.8{\mathrm{Scm}}^{2}{\mathrm{mol}}^{-1}$  The ${\mathrm{\Lambda }}_{\mathrm{m}}^{\mathrm{\infty }}\left[\mathrm{Fe}\left(\mathrm{CN}{\right)}_{6}^{3-}\right]$ will be

1. A

2. B

3. C

4. D

Fill Out the Form for Expert Academic Guidance!l

+91

Live ClassesBooksTest SeriesSelf Learning

Verify OTP Code (required)

### Solution:

${\mathrm{\Lambda }}_{\mathrm{m}}\left({\mathrm{Zn}}_{3}{\left[\mathrm{Fe}\left(\mathrm{CN}{\right)}_{6}\right]}_{2}\right)=3{\lambda }_{\mathrm{m}}\left({\mathrm{Zn}}^{2+}\right)+2{\lambda }_{\mathrm{m}}\left(\mathrm{Fe}\left(\mathrm{CN}{\right)}_{6}^{3-}\right)$ $=3×2{\lambda }_{\mathrm{m}}\left(\frac{1}{2}{\mathrm{Zn}}^{2+}\right)+2{\lambda }_{\mathrm{m}}\left(\mathrm{Fe}\left(\mathrm{CN}{\right)}_{6}^{3-}\right)$ or ${\lambda }_{\mathrm{m}}\left(\mathrm{Fe}\left(\mathrm{CN}{\right)}_{6}^{3-}\right)=\frac{1}{2}\left[{\mathrm{\Lambda }}_{\mathrm{m}}\left({\mathrm{Zn}}_{3}{\left[\mathrm{Fe}\left(\mathrm{CN}{\right)}_{6}\right]}_{2}\right)-6{\lambda }_{\mathrm{m}}\left(\frac{1}{2}{\mathrm{Zn}}^{2+}\right)\right]=\frac{1}{2}\left[922.8-6×52.8\right]{\mathrm{Scm}}^{2}{\mathrm{mol}}^{-1}=303\mathrm{S}{\mathrm{cm}}^{2}{\mathrm{mol}}^{-1}$

+91

Live ClassesBooksTest SeriesSelf Learning

Verify OTP Code (required)